PEMANFAATAN MEDIA PEMBELAJARAN BERANIMASI DALAM UPAYA MEMINIMALISIR MISKONSEPSI PADA MATA PELAJARAN IPA DI SEKOLAH DASAR - Firdaus Muqarrobin, Tamman (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2022)
This study aims to 1) utilize existing learning media in preventing misconceptions in students. 2) Integrating learning media with problem-based learning models can make students' understanding avoid erroneous concepts. 3) Train students to be able to solve problems related to natural phenomena around them using the scientific method. This study uses a One-shot Case Study Research Design where only one class is used as the research subject. The sample used in this study was grade 5 students at public elementary schools in widodaren. Data were collected using observation methods and test instruments at the end of the activity. The results obtained in this study are 1) by using learning media, it can prevent conceptual errors that may occur in students, 2) animated learning media combined with problem-based learning methods can prevent students from learning concepts, 3) with problem-based learning method, students become more accustomed to solving problems using the scientific method..